Blended Learning in Technical and Vocational Education and Training (TVET) Training Institute - Norliza Hashim; Zahari Hamidon (Human Resource Management Academic Research Society, 2022)
This paper discusses blended learning in Technical and Vocational Education and Training (TVET) Training Institute. Blended learning is an approach of teaching and learning that combines different technologies and methods to improve the educational experience in TVET. Blended learning in TVET can be categorised into three models; learning in classroom and workshop enhanced with technology, on- the-job training supplemented with classroom, distance and online learning as well as fully distance and online learning. ADDIE model is applied alongside Google Classroom as a blended learning platform in TVET institution as an initiative to meet the challenges of 21st century learning skills. During the COVID-19 pandemic, most of the TVET institutions implement blended learning method to conduct their training and theory courses online. (Abstract by authors)